Per Formare Ad Una Corretta Sensibilità Liturgica = Forming to a correct liturgical sensibility - Meneghetti, Antonella (Rivista di scienze dell'educazione, 2017)
To intelligently dwell within our times, the Church has felt the need to return to the generative womb of our faith, to celebrate and to learn the original languages for expressing the act of faith. Beginning with the Guidelines for Announcing and Catechizing in Italy (2014), this article presents an historical overview of liturgical renewal using the Italian Pastoral Documents that regularly come out every 10 years, highlight the gradual, continual educative process present in these documents. (English)